Compliance with Religious and State Laws: The Practice of Dual and Single Marriage Contracts within the Shi’i Community - Nur Hidayah, Okti (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
This article portrays the practice of dual and single marriage ceremonies within the Shi’i community in Indonesia, particularly in the context of compliance with both religious and state law. Data were primarily collected through interviews with members of the Shi’i community. The study reveals that both dual and single marriage ceremonies are influenced by actors’ attitude toward the integration of Ja'fari madhab and state law. Individuals who adhere to Ja'fari madhab tend to perform dual marriage ceremonies to satisfy both religious and state legal requirements, whereas those who do not prioritize Ja'fari madhab opt for single marriage ceremonies in compliance with state law. Structurally, the implementation of dual and single marriage ceremonies is shaped by the different rules between Ja'fari madhab and state law. [Artikel ini membahas praktik akad nikah ganda dan akad nikah tunggal di kalangan komunitas Syiah di Indonesia dalam konteks kepatuhan terhadap hukum agama dan negara. Data umumnya dikumpulkan melalui wawancara langsung dengan anggota komunitas Syiah. Penelitian ini mengungkapkan bahwa praktik akad nikah baik ganda maupun tunggal dipengaruhi oleh keinginan menjalankan fikih Ja’fari dan ketentuan hukum negara. Seseorang yang mengakomodir fikih Ja’fari cenderung melakukan akad nikah ganda untuk memenuhi tuntutan agama dan hukum negara; sebaliknya yang tidak mengakomodir memilih akad nikah tunggal untuk mematuhi hukum negara. Secara struktural, pelaksanaan akad nikah ganda maupun tunggal dipengaruhi oleh sikap terhadap aturan agama dan negara yang berbeda antara fikih ja’fari dan fikih negara.]